Age at menopause, motives for consultation and symptoms reported by 40–59-year-old Mexican women. (August 2013) - Legorreta, D.; Montaño, J. A.; Hernández, I.; Salinas, C.; Hernández-Bueno, J. A.; ,
Abstract Objectives To assess the mean age at natural menopause, primary initial motives for consultation, symptoms and factors related to a more severe symptom profile using the Menopause Rating Scale (MRS) in a nationwide sample of middle-aged women in gynecological clinics in Mexico. Methods A total of 4548 women, 40–59 years old were surveyed in gynecological clinics throughout all regions in Mexico. Results The mean age at natural menopause was 47.9 ± 3.82 years. The primary initial motive for consultation was a preventive examination (40.3%). Significant differences (p values by ANOVA) were observed for the mean total and subscale MRS scores, with the exception of urogenital symptoms, between women in the sub-samples from different Mexican regions. The highest mean MRS total scores were observed for women living in the South (9.08 ± 8.20) and the Center-East (8.55 ± 6.74) regions. The national mean MRS total score was 8.19 ± 6.82. An MRS total score ≥ 17, which is considered severe, was observed for 5.2% of women with a regular cycle, 10.5% with more than 7 days of irregularity, 22.6% with more than two absent cycles, 13.1% that had undergone natural menopause, 16% with a hysterectomy, and 21.2% with a bilateral oophorectomy. The five most frequently reported symptoms were: physical and mental exhaustion (61%), irritability (54.2%), depressive mood (54.2%), sleeping problems (53.3%), joint and muscular discomfort (52.8%). Conclusions Differences in the prevalence and severity of MRS symptoms were observed for women from different Mexican regions. MRS symptoms were more frequent and severe in women who had undergone a bilateral oophorectomy or with more than two absent cycles.